2022
DOI: 10.3389/fclim.2022.798618
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Modeling Approach for Probabilistic Assessments of Present-Day and Future Fluvial Flooding

Abstract: Risk-informed flood risk management requires a comprehensive and quantitative risk assessment, which often demands multiple (thousands of) river and flood model simulations. Performing such a large number of model simulations is a challenge, especially for large, complex river systems (e.g., Mekong) due to the associated computational and resource demands. This article presents an efficient probabilistic modeling approach that combines a simplified 1D hydrodynamic model for the entire Mekong Delta with a detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…For flood hazards, it can therefore be understood to mean "susceptibility to damage" posed by floodwaters, with the inundation level acting as the independent variable. Additionally, floodwater type (e.g., saltwater, freshwater, contaminated water) and duration of inundation are also key parameters in the ultimate effects of flooding (Ngo et al, 2022).…”
Section: Concept Of Vulnerabilitymentioning
confidence: 99%
“…For flood hazards, it can therefore be understood to mean "susceptibility to damage" posed by floodwaters, with the inundation level acting as the independent variable. Additionally, floodwater type (e.g., saltwater, freshwater, contaminated water) and duration of inundation are also key parameters in the ultimate effects of flooding (Ngo et al, 2022).…”
Section: Concept Of Vulnerabilitymentioning
confidence: 99%
“…For flood hazards, it can therefore be understood to mean "susceptibility to damage" posed by floodwaters, with the inundation level acting as the independent variable. Additionally, floodwater type (e.g., saltwater, freshwater, contaminated water) and duration of inundation are also key parameters in the ultimate effects of flooding (Ngo et al, 2022). In turn, a thorough vulnerability assessment involves examining system elements and design, as well as identifying component failure modes in response to a given set of threats (Baker, 2005;Peterson et al, 2019).…”
Section: Development Of Vap Framework Concept Of Vulnerabilitymentioning
confidence: 99%
“…Many studies simulating surface flow have been conducted for small urban catchments [29][30][31][32][33][34][35][36][37][38]. Other larger-scale studies have focused on the flood risk from rivers (fluvial flooding) [39][40][41][42]. The first attempt to simulate the flood impacts in European cities was presented by Guerreiro et al [43], where they calculated the percentage of urban areas flooded for 571 cities in Europe with a spatial resolution DTM of 25 × 25 m for nine different rainfall events, but concluded that the low resolution of the DTM imposed major limitations due to not representing flow paths accurately.…”
Section: Introductionmentioning
confidence: 99%